Spending on farms ripples into the region: agritourism impacts - Dhungana, Purushottam; Khanal, Aditya R. (Frontiers in Environmental Economics, 2023)
Introduction/Purpose Agritourism is gaining popularity throughout the United States and is an important part of rural and regional development. However, the economic contributions of agritourism, the interface of agriculture and tourism, has received limited attention in regional impact estimation studies. This study was purposed to estimates the regional economic impact of visitor spending in agritourism farms in Tennessee. Methods Primary survey data was used from sampled farms in Tennessee and secondary industry-level data. Economic impacts—direct, indirect, and induced—are estimated based on the economic input-output modeling application (IMPLAN) and the social accounting matrix framework. Result and discussion We found that an estimated $65 million from visitors' direct spending in agritourism farms contributes to the total industry output of $118.54 million in Tennessee. Additionally, we presented total value added, jobs created, labor incomes, and taxes generated through direct, indirect, and induced effects attributable to visitors' spending in agritourism farms. Our findings indicate that the expansion of agritourism could bring economic development at both the farm and state level, particularly in states like Tennessee, where agriculture is an important industry and tourism is expanding.